BLDC Motor Driven, PSO Optimized 2-DOF PID Control of the Seesaw Balance System - Cukdar, Ibrahim; Yigit, Tevfik; Celik, Hakan (Institute of Electrical and Electronics Engineers Inc., 2021)
In this study, stability control of a 2-rotor unmanned aerial vehicle (UAV), for which various test studies have been continued recently for its use in the field of logistics, was carried out. Brushless Direct Current Motor (BLDC) used as drive element and Seesaw balance system in the study is modeled in Matlab/Simulink environment. The seesaw balance system is important for the analyzing to multi-rotor systems basically and being basis of the Synchropter UAV systems. The created 2-rotor Seesaw balance system model was run with both classical PID and two degrees of freedom (2-DOF) PID controllers and the results were compared. The parameters of 2-DOF PID and classical PID controllers used in the study were determined by Particle Swarm Optimization (PSO). When the results obtained from the simulation were examined, it was seen that the 2-DOF PID controller had better performance than the classical PID controller. © 2021 Chamber of Turkish Electrical Engineers.
13th International Conference on Electrical and Electronics Engineering, ELECO 2021 -- 25 November 2021 through 27 November 2021 -- Virtual, Bursa -- 176537
Keywords: AC motors; Antennas; Controllers; Degrees of freedom (mechanics); Electric control equipment; Electric machine control; MATLAB; Particle swarm optimization (PSO); Proportional control systems; Three term control systems; Unmanned aerial vehicles (UAV); Balance systems; Brushless direct current motor; MATLAB/Simulink environment; Multi rotors system; PID controllers; Stability control; System models; Test study; Two-degree-of-freedom; Unmanned aerial vehicle systems; Brushless DC motors